Logical foundations of Web ontologies - Barber, Elsa E.; Pisano, Silvia; Romagnoli, Sandra; de Pedro, Gabriela; Gregui, Carolina; Blanco, Nancy (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
The article defines the ontologies in the Semantic Web, where they are described as representational artifacts, hierarchical devices constituted by entities and relationships, and are typified according to their degree of generality and functionality. It highlights the basic principles that govern them and good practices to be taken into account at the logical level for their design and implementation in accordance with the Basic Formal Ontology (BFO) oriented to support the logical issues of all types of ontologies. It defines the classes that BFO includes, its relationships and main axioms. It emphasizes the impact of the expressiveness of the languages used when designing ontologies in terms of the resolution of formal aspects that influence the ability of these to generate inferences automatically.